Stakeholders’ perspectives on the success criteria for public-private partnership projects - Osei-Kyei, Robert; Chan, Albert P. C. (International Journal of Strategic Property Management, 2018)
Given the complexity and wide stakeholder interests in public-private partnership (PPP) projects, different parties have different expectations and definitions of PPP project success. This paper explores the perceptual differences on the success criteria for PPP projects among PPP stakeholders. A questionnaire survey was conducted with targeted international PPP experts from the academic, public and private sectors. The research findings show that each stakeholder group considers effective risk management as the most critical success criterion. Moreover, the public and private sectors consider meeting output specifications as the second most critical criteria, whereas the academic sector considers satisfying the need for public facility/service. Further analysis using non parametric tests shows significant differences on the ranking of the criterion, “satisfying the need for public facility/service” between the public and private sectors and between academic and private sectors. These research outputs provide significant insights into how PPP projects’ success is evaluated by various PPP stakeholders.